2014
DOI: 10.1111/eea.12202
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory adaptation reduces female mating resistance in the sweet potato weevil

Abstract: Selection for genetic adaptation might occur whenever an animal colony is maintained in the laboratory. The laboratory adaptation of behavior such as foraging, dispersal ability, and mating competitiveness often causes difficulties in the maintenance of biological control agents and other beneficial organisms used in procedures such as the sterile insect technique (SIT). Sweet potato weevil, Cylas formicarius (Summers) (Coleoptera: Brentidae), is an important pest in sub‐tropical and tropical regions. An eradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…We found that adult males and females of the old colony had higher mating propensity (except for the experiment in groups in which only female origin significantly influenced mating propensity). Similar patterns have been reported in sweet potato weevil Cylas formicarius (Summers) (Coleoptera: Brentidae) by Kuriwada et al (2014), in which mass-reared females exhibited weaker resistance to male mating attempts when compared with females of a wild strain. These effects of domestication may be related to high rearing population density.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that adult males and females of the old colony had higher mating propensity (except for the experiment in groups in which only female origin significantly influenced mating propensity). Similar patterns have been reported in sweet potato weevil Cylas formicarius (Summers) (Coleoptera: Brentidae) by Kuriwada et al (2014), in which mass-reared females exhibited weaker resistance to male mating attempts when compared with females of a wild strain. These effects of domestication may be related to high rearing population density.…”
Section: Discussionsupporting
confidence: 78%
“…Similar patterns have been reported in sweet potato weevil Cylas formicarius (Summers) (Coleoptera: Brentidae) by Kuriwada et al . (2014), in which mass‐reared females exhibited weaker resistance to male mating attempts when compared with females of a wild strain. These effects of domestication may be related to high rearing population density.…”
Section: Discussionmentioning
confidence: 99%